Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

Facilitated lithium storage in hierarchical microsphere of Cu2S-MoS2 ultrathin nanosheets - Kadam, Sunil R.; Kalubarme, Ramchandra S.; Deshmukh, Shrutika P.; Panmand, Rajendra P.; Kawade, Ujjwala, V.; Kulkarni, Milind, V.; Deo, Shriniwas S.; Gosavi, Suresh W.; Kale, Bharat B. (ChemistrySelect, 2018)
Considering the high energy density Lithium ion batteries have become one of the best option for next-generation energystorage technologies. Transition metal chalcogenide nanomaterials are promising electrodes for Lithium-ion batteries. Molybdenum based layered chalcogenide materials wisely studied for rechargeable Li-ion batteries, due to its two-dimensional (2D) layered structure and better specific capacity. The three-dimensional (3D) synthesis of microsphere by ultrathin nanosheets is necessary for practical applications. Herein, the fabrication of a unique hierarchical 2D layered Cu2S-MoS2 nanostructure was (ultrathin nanosheets) demonstrated via in situ assembling of two-dimensional (2D) growths in facile solvothermal technique. The structural study reveals the existence of Cubic Cu2S and Rhombohedral MoS2 phase. Morphological study by FESEM and TEM shows unique ultrathin nanosheets of similar to 10 nm thickness self-assembled in the form of layered microsphere. In Li- ion storage testing, Cu2S-MoS2 electrode exhibited good specific discharge capacity of 651 mAhg(-1) at 50 mAg(-1) applied current and maintained 320 mAhg(-1) after 100 cycles. The facilitated advanced electrochemical performance attributed to layered ultrathin Cu2S-MoS2 composite nanosheets.

MoS2 and CdMoS4 nanostructure-based UV light photodetectors - Pawar, Mahendra S.; Kadam, Sunil R.; Kale, Bharat B.; Late, Dattatray J. (Nanoscale Advances, 2021)
We have developed MoS2 nanosheets and CdMoS4 hierarchical nanostructures based on a UV light photodetector. The surface morphologies of the as-prepared samples were investigated via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The performance parameters for the present photodetectors are investigated under the illumination of UV light having a wavelength of similar to 385 nm. Upon the illumination of UV light, the CdMoS4-based photodetector device showed a better response to UV light compared to the MoS2 device in terms of photoresponsivity, response time (similar to 72 s) and recovery time (similar to 94 s). Our results reveal that CdMoS4 hierarchical nanostructures are practical for enhancing the device performance.